Psychometric properties of a questionnaire on medical students’ satisfaction with a community health program - Alzayani, Salman; Almarabheh, Amer; Al-Roomi, Khaldoon; Alsayyad, Adel (Intelektual Pustaka Media Utama, 2024)
Changes in the learning modes during the recent COVID-19 pandemic has provided a need to construct a feedback questionnaire to measure medical students’ satisfaction with community-based health programs. A total of 551 forms which has a 5-point Likert scale were submitted by the medical students upon concluding the public health program in 2018-2021 (which includes face-to-face and virtual learning). Reliability coefficients were estimated for each factor (domain) with values >0.70. Exploratory factor analysis (EFA) was used to assess the validity of the instrument, using principal components analysis with varimax rotation. EFA identified two factors; the first included 6 items (67.031%) of the total variance, the second explained 4 items (10.114%) and together explained 77.15%. root mean squared error of approximation (RMSEA): 0.074; normed fit index (NFI): 0.975; comparative fit index (CFI): 0.981; incremental fit index (IFI): 0.981; goodness of fit index (GFI): 0.956; Tucker Lewis index (TLI): 0.972. The overall students’ satisfaction had a Cronbach’s alpha test of 0.945 with a 95% confidence interval (0.938-0.952), and a reliability using Guttman Split-Half for overall was 0.894. Students’ satisfaction questionnaire with the public health program has a good reliability and validity in contrasting educational situations and it is worthwhile to include as part of the quality improvement.